Mapping genes for resistance to gastrointestinal nematodes - Behnke, J.M.; Lowe, A.; Menge, M.; Iraqi, F.A.; Wakelin, D. (2000)
GI nematodes are most commonly controlled by chemotherapy. Anthelmintic efficacy is decreasing as drug resistance becomes widespread and other approaches are needed. Knowledge of protective immunity against GI parasites is important for the development of vaccine strategies. Success in this field is presently limited, and parasites have many ways of evading immunity. An alternative approach is selection and breeding of genetically resistant stock. This requires definition of the genes responsible and identification of markers for selection. It is well known that resistance to infection is variable within host species but little progress has been made in defining the genes responsible. We describe an approach to identifying the genes responsible for resistance of mice to Heligmosomoides polygyrus as a model for identification of homologous genes in domestic animals. F2 and eventually F6 generations from crosses between resistant SWR and susceptible CBA strains are being phenotyped for parasitological and immunological traits. Microsatellite mapping will then identify the chromosomal locations and eventually the specific loci concerned. Data from this project will facilitate breeding programmes and lead to a greater understanding of the roles of specific genes and their products in particular resistance mechanisms.